Languages of watson-crick petri net - Mohamad Jan, Nurhidaya; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (Universiti Teknologi Malaysia, 2014)
Watson-Crick automata are one of the automata types that are used for transitions with two reading heads. This automata work on double stranded sequences related by a complementarity relation similar with the Watson-Crick complementarity of DNA molecules. Watson-Crick automata can be related to a Petri net, which is a graphical and mathematical formalism suitable for the modeling and analysis of concurrent, asynchronous and distributed systems. From the relation between Watson-Crick automata and Petri net, a new model namely Watson-Crick Petri net has been developed. In this paper, a new variant of Watson-Crick automata with Petri net as a control unit is introduced. We also presented various types of Watson-Crick Petri nets that are generated using transitions labelled with various labeling policies and finite sets of final markings.